Comparison of Mechanical Properties and Sensitivity of Compressive and Flexural Strength of Artificial Frozen Sand. (10th November 2022) - Chen, Junhao; Li, Han; Lian, Lijin; Lu, Gen
Abstract : Some zones of freezing curtains of subway contact channels are subjected to compression and tension. Thus, understanding the mechanical properties and relationship between the compressive and flexural strengths of frozen soil is crucial. In this regard, this study considered sandy soil from Fuzhou as an example to perform uniaxial compressive and three-point flexural strength tests under different moisture content and curing conditions. The results showed that the uniaxial compressive and three-point flexural strengths of frozen soil were directly correlated with the moisture content and inversely correlated with curing temperature. Moreover, the compressive strength was significantly higher than the flexural strength, and the ratio was between 1.68 and 3.41. The sensitivity analysis for two factors affecting the strength was performed using the grey correlation analysis method. The moisture content showed a stronger effect on the uniaxial compressive strength of frozen sand. In contrast, the curing temperature substantially affected the three-point flexural strength. This study provides a reference for optimizing the freezing scheme for subway connection channels.